Compartilhamento de responsabilidades harmônicas: implementação de Benchmark do IEEE e aplicação de metodologias - Gianesini, Bárbara Morais (2020)
In recent years, the intensification of harmonic distortions on electric power systems has mainly occurred due to the continuous connection of non-linear devices into the grid. It is well-known that the global harmonic distortion at the point of common coupling arises from the interaction among different disturbance sources connected to the network. Therefore, the need to share the harmonic responsibility among the agents involved emerges as a relevant topic and it should be carried out through accurate, reliable and practical procedures. Even though several achievements have been reached in this line of research, as it currently stands, there is no consensus in the literature on the most reliable procedure to cope with this matter. Along with researches concerning the responsibility sharing methodologies, the establishment of test systems to assess these methods also emerges as a relevant task. In this context, the IEEE-PES Task Force on Harmonics Modelling and Simulation has developed a benchmark test system for assessing harmonic contribution determination procedures, called IEEE-HCD Benchmark, which was originally provided on the PSCAD software. Thus, this thesis aims to cooperate with advances in this matter, through the implementation of the Benchmark test system on Simulink/MATLAB software. Simulink was chosen since this platform is widely used by the international scientific community and also by the Power Quality Research Group of the Federal University of Uberlandia. In this way, in order to verify if the implementation is consistent, the simulation results are compared to the expected results given in the original publication. Moreover, along with procedures for estimating harmonic impedances based on the current injection approach, the most popular methodologies for determining harmonic responsibilities are evaluated using the Benchmark.